Notes on happiness in consumer societies - Castellanos-Alvarenga, Luis Mario (2023)
Introduction: Beliefs about happiness and individual success are constructed through social interactions, as individuals set goals in alignment with societal expectations. Objective: This study aims to analyze beliefs about happiness and individual success from both psychological and sociological perspectives. Method: The analytical-synthetic method was employed in the preparation of this essay. Results: The predominant content in beliefs about happiness pertains to material values, reinforcing the notion that success is closely linked to material possessions. Nevertheless, it is crucial to contemplate the significance of non-material factors, such as health, family, and friendships, among others. Conclusion: Individual happiness and success transcend the material plane; because the way in which we process information and construct value judgments about life also plays a fundamental role on them.